The politics of sexuality - Dank, Barry M. (Transaction Publishers, 2000)
Sexuality and Culture serves as a compelling forum for the analysis of ethical, cultural, psychological, social, and political issues related to sexual relationships and sexual behavior. These issues include, but are not limited to: sexual consent and sexual responsibility; sexual harassment and freedom of speech and association; sexual privacy; censorship and pornography; impact of film/literature on sexual relationships; and university and governmental regulation of intimate relationships. The central theme of this volume is the politics of sexuality. Theoretical essays, research reports, and book reviews examine the topics of sexual harassment law as a sexual control mechanism, censorship of sexual materials, and criminalization of commercialized sexuality. A special section focuses on the Clinton-Lewinsky affair with contributions by David Steinberg, John Furedy, and Joseph Fulda. Other articles include: "Trends Towards Increased Sexual Repression in the Final Two Decades of the Twentieth Century" by Elizabeth Allgeier; "Naked but Unseen: Sex and labor conflict in San Francisco's Adult Entertainment Theaters" by Kerwin Kay; "A test of the Biopolitics Hypothesis" by Kenneth Westhues; "Scientific and Fictive Sociology: The Viability of Research" by Edwina Taborsky and Reena Sommer; and "Sex Entertainment for Women on the Web" by Marjorie Kibby. Also included are reviews of books, including Faculty-Student Sexual Involvement: Issues and Interventions, by Virginia Stamler and Gerald Stone; Heterophobia: Sexual Harassment and the Future of Feminism, by Daphne Patai; Sex among Allies: Military Prostitution in US-Korea Relations, by Katharine H. Moon; and American Homo by Jeffrey Escoffier. The Politics of Sexuality will be of interest to general readers as well as to scholars (sociologists, psychologists, legal analysts), policymakers, and members of the sex work and sex entertainment communities.